2009 34th IEEE Photovoltaic Specialists Conference (PVSC) 2009
DOI: 10.1109/pvsc.2009.5411127
|View full text |Cite
|
Sign up to set email alerts
|

Industrial type passivation on interdigitated back junction solar cells

Abstract: Interdigitated Back Junction (IBJ) solar cells are suited to be realized on thin wafers, since they need a combination of high diffusion lengths and thin substrates. Here we present an industrial type passivation stack at the rear surface of an IBJ solar cell, consisting of a low quality SiO2 and a SiNx layer, which has proven its value in the i-PERC concept developed at IMEC. QuasiSteady-State Photo Conductance (QSSPC) lifetime measurements indicate an improvement of lifetime from 10µs to 180µs after applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The type of cells used for the first trials are interdigitated backcontact solar cells, with specifications as shown in Fig. 11, some more information on these cells can be found in [22].…”
Section: Resultsmentioning
confidence: 99%
“…The type of cells used for the first trials are interdigitated backcontact solar cells, with specifications as shown in Fig. 11, some more information on these cells can be found in [22].…”
Section: Resultsmentioning
confidence: 99%
“…The type of cells used for the first trials are IBC solar cells, made in-house (imec) and with specifications as shown in Figure 6, some more information on these cells can be found in [16]. The module was then metallized with the low-temperature Ag paste by means of "manual" screenprinting through a 25-µm PI (polyimide) "shadowmask", and tabs were contact welded to this metallization.…”
Section: Resultsmentioning
confidence: 99%
“…Several proofs of concept of silicone bonding and encapsulation have been demonstrated and are depicted in Figure : on wafers as thin as 40 µm , on 100‐µm‐thin 2 × 2 cm 2 interdigitated back contact (IBC) cells , and on standard metal wrap‐through cells from Photovoltech , each time using silicones from Dow Corning. For the latter case, reliability tests have been carried out to evaluate the silicone encapsulation scheme (cells are interconnected by soldering): 1000 h of damp heat, 200 thermal cycles and 10 humidity freeze cycles according to the specifications in the IEC61215 standard were passed successfully (less than 5% degradation).…”
Section: Fabrication Of High‐quality Crystalline Si Layer On Glassmentioning
confidence: 99%